Electrospinning of Polycaprolactone (PCL) and Gelatin Polymeric Fibers / Shing Chee Lim ...[et al.] - Shing, Chee Lim; Weily, Khoo; Ching, Theng Koh (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Electrospinning is one of the commonly used polymeric fiber production technique, owing to its versatility and flexibility in spinning a wide range of polymers for various applications including tissue engineering. However, recent researches have been extensively focusing on exploring the electrospinnability of different polymers without fully realizing how the electrospinning parameters influence the electrospun fibrous structure, as the microstructure morphology will significantly affect the performance of electrospun membranes. The present work demonstrates the robustness of electrospinning technique in producing electrospun fibrous membranes with different microstructure morphology by altering the electrospinning parameters. Both PCL and gelatin solutions have been successfully transformed into electrospun fibrous membranes using an electrospinning machine. The PCL fibrous membranes consisted of beads and non-homogenous fibers while the gelatin membranes showed homogenous size of electrospun fibers. Results also revealed that the electrospinning parameters including solution and process parameters determined the microstructure morphology of electrospun membrane. The spindle-like beads in PCL membrane transformed into spherical size at higher solution concentration and applied voltage. Meanwhile, the gelatin membrane demonstrated similar morphology at different tip-collector distance. The size of gelatin fibers was also similar. Through this work, basic understanding on how the electrospinning parameters affect the morphology of different types of polymeric fibrous membrane can provide an insight for other researchers in facilitate production of electrospun membranes with desired microstructure morphology.